SISTEM ADMINISTRASI JARINGAN MENGGUNAKAN WINDOWS SERVER 2008 - Alcianno G. Gani; Noor Permadi (Fakultas Ilmu Komputer dan Desain - Unsurya, 2020)
The growth and development of information technology today is getting more and more advanced, especially with the existence of a tool that can make it easier for humans to work more effectively and efficiently, namely computers. In every field, both in government and private agencies, information technology has been widely used. With the existence of information technology with computers as a medium, various jobs and activities will be easier and faster. One implementation of information technology is computer networks supported by internet services. With the existence of internet technology, the gate of the globalization era of information is wide open, this is increasingly encouraging people to increase resources in order to compete for the desired position.